Atypical proliferating epidermoid cyst with xanthomatous reaction - Paula Beers, MD; Vladimir Vincek, MD, PhD (Elsevier, 2019)
Proliferating epidermoid cysts, or proliferating epidermal inclusion cysts, are rare tumors characterized by epidermal keratinization and a cyst wall lined by epithelium typically seen in an epidermoid cyst. Though proliferating trichilemmal cysts have been well described in the literature, little has been written about proliferating epidermoid cysts. We report a unique case of a proliferating epidermoid cyst with malignant transformation and associated exuberant xanthomatous reaction. Our case highlights the importance of close histologic evaluation of typically benign cysts. Keywords: Proliferating epidermoid cyst, Epidermal inclusion cyst, Xanthomatous pseudotumor